Synthesis, physical and chemical properties of 3-((5-(hydroxy(phenyl)methine)-4-R-4H-1,2,4-triazole-3-yl)thio)aceto(propane, methylene-о-, m-, p-benzo)nitriles - А. M. Rud; A. G. Kaplaushenko; Yu. M. Kucheryavyi (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Cancer is one of the main problems of the whole world. Statistics shows that over the past 100 years the level of morbidity and mortality in the world due to the oncopathologies has moved from tenth to second place. It takes next position only after the diseases of the cardiovascular system. According to WHO data, 10 million people get sick per year. The scientists from WHO have reported that cancer mortality will increase by 45% till 2030 year compared to the level of 2007 year.